1956
DOI: 10.1021/j150536a022
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Compounds between Lithium and Lead. I. The Structures of Li3Pb and Li7Pb2.

Abstract: The crystal structures of LiaPb and LilPbz have been determined. The LisPb cell is face-centered cubic with a = 6.687 A.; the Li7Pbz cell is hexagonal with a = 4.751 A. and c = 8.589 A. Two other compounds with Li/Pb mole ratios of approximately 2.5 and 4.0 have been characterized by cooling-curve data and by X-ray diffraction patterns. The arrangement of the atoms in LisPb is similar to that in lithium metal with the appropriate number of lithium atoms replaced by lead atoms; LilPbz has a similar but slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…The atomic distances in these compounds, which have been established by many structural determinations (208,209), show that the radii of the lithium and metalloids, especially of the heavier Group III elements, are shrinking. In spite of this equilibration of sizes, investigating authors have not observed a random distribution of the elements with larger phase widths (with the (20) Li3Bi (20), p·Li3Sb (20) Li3Pb (217), Li3 TI (216) LinPbs (218), LinGes (219) LinSns (219), LinSis (220) Li22T1s (208) Li7Pb2 (217) LisPb3 (221) p.LiPb (223), LiTl (222) p'.LiPb (224) Li7Sn, (225), Li7Ge, (226) LiSSn2 (228), Li, . 33Si (227) Lis Tl2 (216) Li7Sn3 (229) Li13SnS (233) Li9Ge4 (231) LilOSi3 (230) Li13Si4 (232) Li13ln3 (234) Li21n (234), Li2Ga (235), Li2 TI (208) Li31n, (216), Li3Ga, (235), Li3A12 (236) LisGa4 (237), Lisln4 (208) Li9A14 (238) LiAI (57), LiGa (14), LiIn (14) exception of LiAI, LiGa, LiIn, and LiTI).…”
Section: Schafermentioning
confidence: 99%
“…The atomic distances in these compounds, which have been established by many structural determinations (208,209), show that the radii of the lithium and metalloids, especially of the heavier Group III elements, are shrinking. In spite of this equilibration of sizes, investigating authors have not observed a random distribution of the elements with larger phase widths (with the (20) Li3Bi (20), p·Li3Sb (20) Li3Pb (217), Li3 TI (216) LinPbs (218), LinGes (219) LinSns (219), LinSis (220) Li22T1s (208) Li7Pb2 (217) LisPb3 (221) p.LiPb (223), LiTl (222) p'.LiPb (224) Li7Sn, (225), Li7Ge, (226) LiSSn2 (228), Li, . 33Si (227) Lis Tl2 (216) Li7Sn3 (229) Li13SnS (233) Li9Ge4 (231) LilOSi3 (230) Li13Si4 (232) Li13ln3 (234) Li21n (234), Li2Ga (235), Li2 TI (208) Li31n, (216), Li3Ga, (235), Li3A12 (236) LisGa4 (237), Lisln4 (208) Li9A14 (238) LiAI (57), LiGa (14), LiIn (14) exception of LiAI, LiGa, LiIn, and LiTI).…”
Section: Schafermentioning
confidence: 99%
“…Hauptgruppe [6][7][8][9][10][11] strukturell durch Varianten der kubisch innenzentrierten Packung (W-Struktur) beschreiben, in der auch das Lithiummetall selbst kristallisiert. Das Natrium bildet ebenfalls diese Struktur aus.…”
Section: Einführungunclassified
“…Each lithium atom has a nearest-neighbor environment of eight tin atoms in the form of slightly compressed cubes. Similar distorted cubes occur already in the binary lithium stannides [13] and plumbides [40][41][42][43][44]. The various coordination polyhedra have been summarized by Frank and Müller [13].…”
Section: Crystal Chemistry and Chemical Bondingmentioning
confidence: 53%